Electric Vehicle based on standard industrial components - Fernández-Ramos, José; Aghili-Kathir, Foroohar (My University, 2013)
The aim of this paper is to presents the complete design of an electric vehicle by using standard industrial components as VRLA batteries, AC induction motors and standard frequency converters. In comparison with dedicated components, the use of standard components has the following advantages: higher reliability, low price, broad range of products and suppliers, and high availability and technological independence. Besides this, we show that these components allow to make an easy and efficient electric differential without speed or steering
Keywords: Vehículos eléctricos; Electric vehicle; Electric differential; Standard frequency converter; AC induction motor